METHODS OF DEVELOPMENT OF PRACTICAL SCIENCES OF STUDENTS IN THE PROGRESS OF EDUCATION - Ў. Д. Хидиров (American Journals, 2023)
This article describes the development of students' practical knowledge in the educational process, the effectiveness of practical training and the qualities of preparing students for practical training.
Keywords: In the Republic of Uzbekistan, higher education, practical training.